(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the influence of low acyl (LA) and high acyl gellan gum (HA) and honey on the physical-chemical and sensorial characteristics of mango and cashew apple structured fruits. The samples were made with honey (CM) and without honey (SM), in a 5% concentration , with 47.5% each mango and cashew apple pulp, and the LA:HA ratios of 100:0, 75:25 and 50:50, in a concentration of 0.75%. Physical and chemical assays (pH, titratable acidity, soluble solids, water activity) and sensory analysis (acceptance, consumption intention and characterization by Check-All-That-Apply-CATA and Rate-All-That-Apply-RATA tests). The physico-chemical characteristics of the samples were very similar, however, soluble solids contents were higher in CM (20.00 °Brix) than SM (12.00 to 13.00 °Brix) formulations. The LA100/HA0 CM sample was best accepted, with overall impression between the terms “slightly liked ” and “moderately liked”, and LA50/HA50 SM was less accepted, with means between the terms “slightly displeased” and “neither liked or disliked”. This probably occurred because the attributes "sweet taste" and "honey taste" were quantified with greater intensity in the LA100/HA0 CM formulation, while "strange taste" was more intense on LA100/HA0, LA75/HA25 and LA50/HA50 SM. It was concluded that the different proportions of LA and HA gel gums did not influence the physical-chemical characteristics of the structured fruits. However, hydrocolloids and honey influenced the sensory characteristics of the product, since the participants best accepted the sample containing honey and a higher proportion of LA gel (LA100/HA0 CM).